A novel fuzzy logic control for a zero current switching-based buck converter to mitigate conducted electromagnetic interference - Zakaria M'barki; Kaoutar Senhaji Rhazi; Youssef Mejdoub (Institute of Advanced Engineering and Science, 2023)
This research provides a new control technique for mitigating conducted electromagnetic interference (EMI) in a buck converter designed for solar applications. Indeed, hard-switching direct current to direct current (DC-DC) converters, commonly used in industrial applications, pose a significant risk to the surrounding environment regarding electromagnetic compatibility (EMC). Usually, the fast-switching phase induces abrupt changes in current and voltage, which adds to substantial electromagnetic interference in both conducted and radiated modes and excessive auditory noise. An architecture based on the duality of soft-switching topology and fuzzy logic control technology is developed to address these issues. On the one hand, resonant circuit topologies are used to induce switches to achieve soft switching conditions, which subsequently lessen the effects of EMI. On the other hand, the adoption of fuzzy logic control technology is interesting since it can reduce electrical stresses during switching. Furthermore, the simulation results show that zero current switching (ZCS) soft-switching closed-loop fuzzy logic converters outperform typical open-loop converters and soft-switching closed-loop converters with proportional integral (PI) control in terms of EMC requirements.